Aetiology of Vertigo as Seen at the Federal Medical Center Lokoja, North Central Nigeria - Stephen Agbomhekhe Ogah (Sudan Journal of Medical Sciences)
Background: Human beings are able to maintain their balance from a combination of proprioceptive, graviceptive, visual and the vestibular inputs integrated by the central nervous system. Hence, symptoms of imbalance can arise whenever there is a defect either in these peripheral sensors or the modulating central nervous system. The prevalence of vertigo is 20-30% and it is a major health issue all over the world.